The Conflict of Balances in the Mediterranean Region and its Repercussions on the Map of the Ottoman-European Conflict in North Africa in the 19th century - Şerifoğlu, Metin; Meshref, Abdullatif (Journal of Ecohumanism, 2025)
This paper explores the imperialist expansion in the Mediterranean basin and its influence on the Ottoman-European conflict map in North Africa during the 19th century. This era marked significant Western imperialist growth across the Mediterranean and Ottoman territories. North Africa became a key battleground where the Ottoman Empire clashed with European powers competing for colonies in the region. Following the Berlin Conference of 1878, the Ottoman Empire recognized the strategic importance of North Africa in resisting European colonial ambitions, particularly their efforts to access Central Africa’s resources by exploiting Ottoman territories. European nations, while united in their imperialist goals, competed fiercely due to divergent interests, leading to international conflicts and shifts in regional balances. This research aims to analyze the nature and background of imperialist expansion in the Mediterranean and its implications for the Ottoman-European conflict. Using a methodology combining deconstruction, historical analysis, and comparative studies, the research draws on Ottoman documents, newspapers, and a range of Turkish, Arab, and Western sources for an objective examination. The findings highlight two key conclusions: first, the imperialist expansion in the Mediterranean was deeply rooted in crusading colonial motives aimed at controlling global resources; second, North Africa played a pivotal role in shaping regional and international dynamics in the late 19th century.